Health Belief Model–Based TRIAD-KRR Education and Risky Sexual Behaviors among Adolescents: A Literature Review - Shinta Ainur Rohmah; Sri Wahyuni; Nopi Nur Khasanah; Herry Susanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Adolescents are a vulnerable group for reproductive health problems, including risky sexual behaviors, sexually transmitted infections, and unintended pregnancy. Theory-based health education, such as the Health Belief Model (HBM) and the TRIAD-KRR framework, is considered effective in improving knowledge, strengthening risk perception, and promoting protective behaviors. However, variations in intervention delivery from face-to-face sessions and peer education to digital platforms require a comprehensive evaluation of their effectiveness. Objective: This literature review aimed to evaluate the effectiveness of theory-based reproductive health education (HBM, TRIAD-KRR, and related approaches) in improving knowledge, attitudes, self-efficacy, and the prevention of risky sexual behaviors among adolescents. Methods: A systematic search was conducted in PubMed, ScienceDirect, Google Scholar, DOAJ, and national journal portals (Garuda, university OJS platforms, and Indonesian nursing and health journals) for articles published between 2020 and 2025. The search strategy followed the PICO framework and PRISMA 2020 guidelines using keywords related to adolescents, TRIAD-KRR, Health Belief Model, health education, and risky sexual behavior. Inclusion criteria were original research articles using quasi-experimental or randomized controlled trial designs, adolescent populations, theory-based educational interventions, and outcomes related to knowledge, attitudes, or risk behaviors. Articles were screened through title–abstract review, full-text assessment, and eligibility verification. A total of 13 studies met the criteria and were appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results: Theory-based educational interventions delivered through classroom teaching, peer-led activities, case-based learning, and digital media consistently improved adolescents’ knowledge, enhanced attitudes and self-efficacy, and reduced tendencies toward risky sexual behaviors. Conclusion: Theory-based reproductive health education is an effective and feasible strategy for preventing risky sexual behaviors among adolescents. Integrating interactive methods with digital support is recommended to sustain and strengthen program outcomes.